War Impacts Studies Using Remote Sensing. - Mansor, Shattri; Mohd Shafri, Helmi Zulhaidi; Al-doski, Jwan (2013)
Since 1960, remote sensing satellite imagery reconnaissance has played a significant role in military operations by providing information concerning enemy missiles, troop deployments and military positioning using photographic images from lighter-than-air balloons to aircraft platforms and finally satellite remote sensing imagery with little attention given to broader war impacts. However, besides the war-related uses of such technology, many academic researchers have taken pains to use such advanced technology for examining war impacts. This paper highlights the applications of this technology for detecting war impacts.